Fragilidade ambiental do município de Guaíra - PR - Bueno, Karoline (2015)
This study is the result of the need for understanding the dynamics of Guaira city s landscape, situated in the western middle region of Paraná state and the recognition of its environmental weaknesses. This understanding becomes relevant, summarily, from the reality of the natural framework of the city that extends over an area of contact and transition between the basaltic rocks of the Serra Geral formation and sandstone rocks of the Caiuá formation, a factor that causes the landscape settings different from fragility. From this, it was aimed to recognize these different settings to better plan the usage and occupation of this territory, in order to not make it even more fragile and unstable before the inadequate anthropic actions that limit the natural environment. For the conclusion of this research it was adopted a methodology proposal developed by the geographer Jurandyr Luciano Sanches Ross (1990-1994) that consists of the usage of the term Potential Instability Ecodynamics Units and Emergent Instability, classified in degrees of fragility. To seek the understanding of these weaknesses it was necessary to map Guaira city s characteristics, considering the local recognition of the geology, land relief and soil, in addition to the mapping of land use. The intersection of the thematic maps with basic information resulted in two synthesis letters representing the outlines of the areas of potential and emerging fragility of the city. Among the conclusions of the survey, the confirmation of a "pre-event" on the potential fragility inherent to the areas of sedimentary rocks stands out, along with soils arising from these rocks, by setting up a greater degree of instability and fragility in the landscape. In relation to the emerging weaknesses identified in the landscape, some inconsistencies in land usage are stated, and that determine, in portions of both lithological covers, character of greater instability, having as determiner in the fragility given other terrain variables such as soil and land relief, combined with agricultural practices of temporary monoculture